SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KETUA HIMAPRODI MENGGUNAKAN METODE WEIGHTED PRODUCT - Yudo Bismo Utomo; Dian Efytra Yuliana; Harso Kurniadi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Himaprodi Tekkom is one of the student organizations at the level of the Computer Engineering Study Program on the Uniska Kediri campus and includes intra-campus organizations as well as extra-curricular activities that can be selected and participated in by each student. The term of office of the chairman of Himaprodi is one year; when the term of office ends, the selection of the new Himaprodi chairman will be held at the time of the musma. In its selection, Himaprodi Tekkom still uses manual methods that make it too time-consuming and less efficient. In order to be effective and efficient, and moreover, the study program is a computer engineering study program, a website-based recommendation system was created to determine the candidate for the new Himaprodi Chairman using the weighted product method as a data processor based on six criteria that have been given, including leadership, wisdom, competence, responsibility, communicativeness, creativity, and innovation. The results achieved from this study were to use the weighted product method, so Arif Nur Huda's name was chosen as the new head of the Himaprodi Teknik Komputer with a value of 0,447.